Genetic Variation through Polymorphism of Blood and Egg White Protein in Three Kinds of Kedu Chickens at Laying Period - Mahfudz, LD; Wulandari, AR; Johari, S (Universitas Jenderal Soedirman, Faculty of Animal Science, Purwokerto-Indonesia, 2011)
Abstract. Genetic variation of five blood protein loci and three egg white protein loci in three kinds of Kedu chicken, namely the black skin and black feather (BB), black skin and white feather (BW) and white skin and white feather (WW) were investigated using polyacrilamide gel electrophoresis. The result showed that five blood loci (pre-albumin, albumin, post-transferin, transferin and hemoglobin) and three egg white loci (lysozim, ovalbumin and conalbumin) were found to be polymorphic in three kinds of Kedu chicken. BW has average higher heterozygosity than BB and WW. The result was shown in blood and egg white protein polymorphism. There was no difference on blood and egg white protein in the genetic variation. The average of heterozygosity of Kedu chicken of high production and low production was not different. Genetic distance among three populations of Kedu chicken showed that Kedu chicken BW was closer to WW than to BB.Key Words: Kedu chicken, protein polymorphism, blood, egg white, genetic variation